K-Means Clustering Algorithm and Architecture: A Brief Survey - Ramakrishan Reddy Eamani, Dr.N.VinodhKumar, Ganga Ramesh Jakkamsetti (International Journal of Advanced Science and Technology, 2020)
Clustering is a technique of grouping the similar items, which is widely used in unsupervised classification. K means is one of the best clustering strategies among all partitioning based clustering strategies which is widely used in clustering due to its uniform effect on the clusters produced with relatively uniform size, though the input data have different size of clusters. This article presents a brief survey on the K-Means clustering Algorithm and its architectures.